2019
DOI: 10.3389/fimmu.2019.00970
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fc Receptor Genetic Diversity on HIV-1 Disease Pathogenesis

Abstract: Fc receptor (FcR) genes collectively have copy number and allelic polymorphisms that have been implicated in multiple inflammatory and autoimmune diseases. This variation might also be involved in etiology of infectious diseases. The protective role of Fc-mediated antibody-function in HIV-1 immunity has led to the investigation of specific polymorphisms in FcR genes on acquisition, disease progression, and vaccine efficacy in natural history cohorts. The purpose of this review is not only to explore these know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 78 publications
1
11
0
Order By: Relevance
“…The copyright holder for this preprint (which this version posted May 15, 2021. ; https://doi.org/10.1101/2021.05.12.443737 doi: bioRxiv preprint study and may potentially be manipulated to improve vaccine efficacy (Chung & Alter, 2017;Geraghty, Thorball, Fellay, & Thomas, 2019;Tay, Wiehe, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted May 15, 2021. ; https://doi.org/10.1101/2021.05.12.443737 doi: bioRxiv preprint study and may potentially be manipulated to improve vaccine efficacy (Chung & Alter, 2017;Geraghty, Thorball, Fellay, & Thomas, 2019;Tay, Wiehe, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a sub-analysis of 467 long-term non-progressors and 517 rapid progressors, there was no association between FcγRIIa polymorphisms and HIV-1 disease progression. Finally, in the same meta-analysis, FcγRIIIa polymorphisms were not associated with HIV-1 disease progression in the Swiss HIV Cohort Study (SHCS) ( 56 ). Although another study found homozygous FcγRIIIa-176V/V to be highly prevalent in HIV progressors on ART compared to untreated natural viral suppressors, they could not conclude on this polymorphism’s association with viral set point ( 47 ).…”
Section: Fcγr Polymorphisms Hiv Disease Progression and Art Outcomesmentioning
confidence: 96%
“…for viral clearance (63,64). When Geraghty et al examined the role of FcgRIIa-(rs1801274) and FcgRIIIa-(rs396991) polymorphisms in 6300 HIV+ adults with European ancestry from a previous GWAS (65), they did not find any association between these polymorphisms and HIV acquisition (56). Furthermore, in the largest study of its kind in Africa, Connolly and colleagues also found no association between FcgRIIa-H131R (rs1801274) and FcgRIIIa-V176F (rs396991) variants and HIV infection or CD4+ T-cell decline in two cohorts in Rwanda and Zambia (50).…”
Section: Fcgr Polymorphisms and The Risk Of Hiv-1 Infection With And Without Vaccinesmentioning
confidence: 99%
See 2 more Smart Citations